Roads to Quoz : an American mosey - Heat Moon, William Least (New York : Little, Brown and Co., 2008)
Heat-Moon writes travel books like no one else. Quirky, discursive, endlessly curious, he embarks on American journeys off the beaten path. Sticking to the small places via the small roads, he uncovers a nation deep in character, story, and charm. "Quoz" refers to anything strange, incongruous, or peculiar. Quoz can be history and heredity; stories, retold or invented; strange characters with poignant dreams. It's places with names like Sublimity City, Kentucky, and Dull Center, Wyoming; unresolved crimes, violent and rippling; schemers and inventors and those missing a tooth or two; and the mysterious Quapaw Ghost Light of Oklahoma. For the first time since his 1982 Blue Highways, Heat-Moon is back on the backroads with a lyrical, funny, and magisterially told chronicle of American passage, of maps of the heart and mind.
Down an ancient valley -- Into the Southeast -- Into the Southwest -- Into the Northeast -- Into the Northwest -- Down an old waterway -- Valedictories.
Includes index.
Keywords: Heat Moon, William Least -- Travel -- United States -- Anecdotes; United States -- Description and travel -- Anecdotes